High Interstitial Stainless Austenitic Steels - Berns, Hans.; Gavriljuk, Valentin; Riedner, Sascha; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
High Interstitial Stainless Austenitic Steels is of interest to all engineers and resaerchers working with stainless steel, either at universities or R&D departments in Industry. The new applications described appeal to design engineers while procees engineers find interesting challenges. These novel steels enter more and more industrial applications. Their development is presented by this book in its entirety, starting from the electronic scale of components. This makes it particlularly attractive to Materials Scientists and Metal Physicists.
Constitution -- Structure -- Properties -- Manufacture -- Assessment.
Keywords: Structural control (Engineering).; Materials; Materials Science; Metallic Materials; Structural Materials; Operating Procedures, Materials Treatment; Energy, general